Utilização da técnica de GPR (Ground Penetrating Radar) para a caracterização de unidades geológicas na cidade de Vitória (Espírito Santo, Sudeste do Brasil) - Rocha, Diego Silva da (2019)
This study aims to characterize, by electromagnetic method, two (2) geological units in the metropolitan region of Vitória-ES, using the GPR- Ground Penetrating Radar technique. Secondary objectives are to investigate lithotypes and geological structures, to delineate contacts between landfills and Precambrian basement, to investigate and describe geological structure arrangements and to demonstrate the geophysical signature of the studied units. The study area corresponds to two (2) geological-geomorphological environments in the city of Vitória (Espírito Santo, Southeastern Brazil): i) campus area of the UFES (Goiabeiras), corresponding to recent sandy and muddy fluvial deposits; ii) Pedra da Cebola area, corresponding to the Vitória Massif. Five (5) geophysical profiles were realized, in different orientations, so that the different subsurface characteristics were approached and represented in the radargram. The profiles had a length of up to 52m (fifty two meters) and were analyzed to the depth of approximately 6m (six meters). The acquisition of GPR was performed with a 270 MHz (two hundred and seventy megahertz) antenna, the walking was performed using the constant distance method where the antennas remain at a constant distance from each other. The GPR profiles were processed through the RADAN7® program, using advanced data processing until the image obtained showed well-defined reflectors and anomalies. The data of the radargrams showed two important geological aspects: limit of very marked geological units and presence of geological structures. Both image line and field measurements showed that NE-SW structures are very well marked, secondarily NNW-SSE and E-W structures. These structures may be associated with lithostructural controls and neotectonic tensions. The method demonstrated an easy and fast application, highlighting here an optimization of time and cost for analysis of material in subsurface